2020
DOI: 10.1039/d0cc01717e
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented formation of reverse micellar vesicles from psuedopeptidic bottlebrush polymers

Abstract: The spherical assemblies named “reverse micellar vesicles” from self-assembling psuedopeptidic bottlebrush polymers are reported. These assemblies exhibited the combined features of both micelles and vesicles viz. molecular arrangement of classical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Ultramicroscopic studies suggested a concentration-dependent assembly with the initial formation of a sheet at low concentration, which eventually bent and mustered to form vesicles at higher concentration. 38 ■ SELF-ASSEMBLING DESIGNER PSEUDOPEPTIDES…”
Section: Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Ultramicroscopic studies suggested a concentration-dependent assembly with the initial formation of a sheet at low concentration, which eventually bent and mustered to form vesicles at higher concentration. 38 ■ SELF-ASSEMBLING DESIGNER PSEUDOPEPTIDES…”
Section: Researchmentioning
confidence: 99%
“…In a totally different approach, self-assembling pseudopeptidic bottlebrush polymers were designed and synthesized. 38 The lipidated amino acid derivatives of the exonorbornene scaffold were polymerized using ring-opening metathesis polymerization (ROMP) by a Grubbs second-generation Ru catalyst to obtain self-assembling bottlebrush polymers. These polymers selfassembled to reverse micellar vesicles in which molecules are arranged like reverse micelles with dimensions similar to those of vesicles.…”
Section: For Vesicular Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…When the hydrophilic head is faced inside while the hydrophobic tails are projected outside, this arrangement refers to a reverse micelle, as shown in Scheme 2 [40,[69][70][71]. The inverse micelle can form a nanostructure or undergo self-assembly in non-aqueous solutions [72].…”
Section: Polymeric Inverse Micellementioning
confidence: 99%